Saint Thomas the Apostle New Testament, Apocrypha, and historical traditions - Thomaskutty, Johnson 1972-; Charlesworth, James H. 1940- (London Oxford New York New Delhi Sydney Bloomsbury T & T Clark, 2018)
Are the Thomas references in the Gospel of John, the Thomas compositions, and the early Thomas traditions in northwestern and southern India purely legendary as biblical scholars have assumed or do they preserve unexamined historical traditions intermittently as the Thomas Christians in India have believed? Didymus Judas Thomas is one of the most misunderstood characters from the beginning of the New Testament history and interpretation. In this study, Thomaskutty addresses the following questions: whether Thomas was merely a `doubting Thomas' or a `genuine Thomas'? Can we understand Thomas comprehensively by bringing the New Testament, apocrypha, and historical traditions together? How was Thomas connected to eastern Christianity and how does the Thomas literature support/not support this connectivity? Can we understand the Thomas traditions related to Judea, Syria, and India with the help of canonical, extra canonical, and traditio-historical documents? Thomaskutty investigates the development of the Thomas literature right from the beginning, examining and questioning the approaches and methodologies that have been employed in interpreting these documents, and analyzes the Thomas literature closely in order to understand the character, his mission involvements, and the possible implications this may have for understanding early Christianity in the east
Includes bibliographical references and indexes
Keywords: Thomas active 1st century -- Thomas active 1st century; Bible -- Criticism, interpretation, etc; Gospel of Thomas (Infancy Gospel) -- Criticism, interpretation, etc; Acts of Thomas -- Criticism, interpretation, etc; Gospel of Thomas (Coptic Gospel) -- Criticism, interpretation, etc -- Acts of Thomas -- Bible -- Gospel of Thomas (Coptic Gospel) -- Gospel of Thomas (Infancy Gospel)